An Objective Identification Method for Wintertime Cold Fronts in Eurasia - Feng, Mengru; Qin, Yujing; Lu, Chuhan (Advances in atmospheric sciences, 2021)
The present study identifies wintertime cold fronts in Eurasia from gridded datasets using a new objective two-step identification scheme. The simple and classic conception of a front is adopted, where a cold front is identified as the warm boundary of the frontal zone with a suitable horizontal temperature gradient and cold advection. We combine the traditional thermal front parameter with temperature advection to first identify the cold frontal zone, and then its eastern and southern boundaries are objectively plotted as a cold front in Eurasia. By comparing different cold front identification methods, the results from this two-step cold front identification method and subjective analysis are more consistent, and the positions of the cold front identified with our method are more reasonable. This objective technique is also applied to a nationwide cold wave event over China. Results show that the horizontal extent and movement of the cold front are in good agreement with the related circulation and the associated cold weather. The proposed method and results in this study may shed light on the rapid identification of cold fronts in operational weather analysis and facilitate further research on the long-term activity characteristics of continental cold fronts.